The relationship between authentic leadership, optimism, self-efficacy and work engagement : an exploratory study - Roux, Shayne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MComm (Industrial Psychology))--University of Stellenbosch, 2010.